Ergonomic evaluation of the risk factors causing pain in the upper part of the body among IT professionals in India. - Sahu, Mona; Gnanaraj Solomon, Darius; Vijay, Santhiyagu Joseph; Sudhahar, Jayaseelan Clement (Work, 2020)
BACKGROUND: In developing countries, the recent increase in computer-related work has considerably increased the occupational complaint of pain. OBJECTIVE: To examine the effects of workstation design, posture and ergonomic awareness on the prevalence of pain for a year in the upper part of the body (eyes, hands, arms, shoulders, lower back, and upper back) among IT professionals in India. METHOD: To investigate the association of risk factors with the prevalence of pain in different body parts, a newly designed online questionnaire titled "A Questionnaire based on ergonomics for IT Professionals" was developed. The psychometric properties of this questionnaire were tested. 110 computer office workers were recruited from IT companies from major cities in India. RESULTS: The confirmation of reliability and lack of redundancy of items was provided by the calculation of internal consistency (Cronbach's alpha 0.804) and cross-validation. 60% of participants was male. Mean age was 29.73±6.09 years. The prevalence of pain for a year in the upper part of the body was 38.2%. The frequently reported pains were in the neck (22.7%), lower back area (22.7%), and eye strain (21.8%). CONCLUSION: It was identified that long working hours, excessive usage of smartphones, lack of exercise, incorrect workstation adjustments, and incorrect posture were the risk factors for the prevalence of pain.